Reconceptualization of Inclusion through Anti-Bias Curriculum - Binnendyk, Sarah (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2022)
Tensions can arise when biased thoughts and practices are uncovered through discursive events in early years classrooms. This paper challenges the common practice of disregarding childhood curiosities in an attempt to ease tension and remove the risk of discomfort for some adults in caregiving and educating roles. Through a conceptual shift from a futurity of inclusion to an urgent call to action that problematizes the exclusion of nonhuman subjects within the curriculum, the construction and implementation of anti-bias curriculum is offered as a vehicle to the realization of holistically inclusive early learning spaces.